1996
DOI: 10.1111/j.1467-9493.1996.tb00080.x
|View full text |Cite
|
Sign up to set email alerts
|

The Retreat of the Forest in Southeast Asia: A Cartographic Assessment

Abstract: Rapid deforestation is a major problem throughout the tropical world. The conditions and the pace under which societies and economies of the Third World are currently evolving and growing, combined with the specificities of tropical forests, render the latter increasingly vulnerable. Among the major tropical areas of the world, Southeast Asia is perhaps the one where these conditions have had the most impact on the retreat of the forest cover over the last quarter of this century. This is illustrated through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…From 1975 to 1995, vegetation cover in the Thai part of the northern catchment did not change in a way that could contribute to the observed runoff decrease. Major land‐cover changes observed in Northern and Central Thailand rather resulted in deforestation (Bernard and De Koninck, 1996) with expected runoff increases (Brown et al , 2005). Contrasting this, hydrological changes that possibly occurred in Myanmar and Vietnam (covering 4% of the study area) would be insignificant at the catchment scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 1975 to 1995, vegetation cover in the Thai part of the northern catchment did not change in a way that could contribute to the observed runoff decrease. Major land‐cover changes observed in Northern and Central Thailand rather resulted in deforestation (Bernard and De Koninck, 1996) with expected runoff increases (Brown et al , 2005). Contrasting this, hydrological changes that possibly occurred in Myanmar and Vietnam (covering 4% of the study area) would be insignificant at the catchment scale.…”
Section: Discussionmentioning
confidence: 99%
“…The Lower Mekong Basin in Southeast Asia has been the scene of major human and environmental upheavals over the last five decades, especially in the Indochinese section (Indochina is defined as the area covered by Cambodia, Laos and Vietnam) where successive political regimes have been accompanied by armed conflicts and significant migrations. The Vietnam War, whether official in Vietnam, or secret in Laos, is invoked as a central explanation for the extensive deforestation observed from 1960 to 1980 in the Lower Mekong Basin (Bernard and De Koninck, 1996). During this conflict, the United States Air Forces (USAF) practised deliberate massive removal of vegetation as a military tactic to deny cover and land to opposition forces (Seig, 1970; Hatfield Consultants Ltd, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Including ‘open forests’ (corresponding to dry forests) the forest cover is 68%, which is an overestimation as almost all highlands, including regions that were settled long before, are considered as forested. The estimate by Bernard & De Koninck (1996) for the end of 1960s derives from several published sources estimating forest cover at global or regional scales. The FAO World Forest Inventory of 1958 (FAO, 1960) is based on data from 1953 for the former North Vietnam.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the forcing of the monsoon, a relationship between the interannual variance of the WNP monsoon and the annual maximum discharge in Kratie is found that explains the variation of the scale parameter. It is however acknowledged that other factors play a role in flood generation, such as land use change (Bernard and Koninck, 1997), land management (Haddeland et al, 2006), dam building (Lauri et al, 2012) and local meteorological conditions (Hsu et al, 2008) that may not be related to the larger monsoon circulation. There is however a point in assessing the impacts of a change in the monsoon regime, since it constitutes the dominant factor for floods in the lower Mekong Basin.…”
Section: The 100-year Flood In Kratie Under CCmentioning
confidence: 99%